Central European preparation for the European integration, lessons for the Western Balkans, in particular Serbia - Becsey, Zsolt László (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
In addition to the author’s scientific work, the study -based on pragmatic experiences -analyzes the factors that characterized Central European countries before the change of regime (1990) and then the foreign economic model through which Poland, Hungary, the Czech Republic and Slovakia reached EU membership in 2004. The study highlighted that ,with different depths, in all countries concerned economic policies were characterized by liberal bankruptcy regulations and strict conditions of competition, so that they could prove their ability to meet the condition of a functioning market economy for EU membership . The export-oriented model, built on efficient inflow of foreign direct investment and high-tec in the early 1990s, was implemented by the late 1990s to demonstrate that these states were ready to meet another condition of EU membership , namely to meet the challenges of the internal market. This transformation represented a problem for the current account balance in the 1990s (mainly due to the loss of traditional national export capacities) only in the middle of the decade, and it was only at the end of the decade that trade balances became active with the EU. The total external equilibrium of the Visegrad countries was maintained by the fact that the inflow of FDI had not yet started to conclude in the withdrawal of profits from recent investments in Central Europe, and the countervailing effect of EU net transfers, which began to arrive later paralelly with the start of the withdrawal of FDI dividends. The CEFTA co-operation concluded in 1992 followed the economic liberalization timetable of that of the Visegrad Four with the EU paralelly, but did not go beyond its depth for political prudence, thus providing full opening to each other only after and through EU membership, concretely the liberalisation in services or in sensitive agricultural trade. The CEFTA treaty was expanded to the Balkans after 1995 and has been and is a good example for countries that do not want to stay in an ex-Soviet or ex-Yugoslav economic integration, but is a good method to prepare for the earliest possible EU membership. Therefore, in the preparation of the Serbian EU acession, it is worthwhile to study the Visegrad experience and lessons - a decade before membership